Educação permanente e suas interfaces com as condições sensíveis à atenção primária - Charlene Ester Machado Silva; Denise Barbosa de Castro Friedrich; Beatriz Francisco Farah; Kênia Lara Silva (Universidade Federal do Ceará, 2017)
Objective: to understand the process of continuing education by primary health care nurses and their interfaces with ambulatory care sensitive conditions. Methods: a qualitative study was carried out with 14 nurses from health units. To collect the data, we used semi-structured interviews and the analysis was carried out through dialectical hermeneutics. Results: two categories emerged: Assistance in primary health care and hospital admissions - which pointed out that the major cause of hospitalizations is related to chronic diseases, and that most of them were preventable; Education: a tool to deal with ambulatory care sensitive conditions - where continuing education is recognized as a tool to interfere in the occurrence of these hospitalizations, but the practices carried out are closer to continuing education. Conclusion: nurses have developed educational processes that are closer to continuing education. The relationship between continuing education and ambulatory care sensitive conditions is still incipient.